Microbiota of a UASB Reactor Treating Palm Oil Mill Effluent Using HiSeq Sequencing - Mohamad Mokhtar, Ibrahim; Zulkifly, Jemaat; Nour, Abdurahman Hamid (Trans Tech Publications, 2021)
Potential microbial communities in the UASB reactor fed with two different substrates i.e synthetic wastewater and raw palm oil mill effluent (POME) were elucidated by using one of the most popular techniques in molecular methods, viz 16S rDNA cloning. The methodology involved; the extraction of nucleic acids, amplification and cloning of the 16S rRNA genes on sequencing HiSeq platform and finally identification and affiliation of the isolated clone with the aid of phylogenetic software. Results showed that the genus methanosarcina and methanosaeta were dominant methanogens in this study for both substrates types. Overall, microbial population (Bacteria and Archaea) in sample A (POME as substrate) is more diverse compared to sample B (synthetic wastewater as substrate) due to abundance of microorganism population in raw POME which was used as a substrate. However for the methanogenic (Archaea) diversity in both samples, there was not much different between sample A and sample B probably due to similar inoculum was inoculated in the reactor despite of have using different substrate type.